(untitled) (Journal of Mathematics Mechanics and Computer Science, 2011)
The reason of it is that there is an extreme restriction of the application of that is Gauss curvature should be strictly positive. On the other hand search for isometrically connected coordinates on the surface of positive curvature with the point of condensation brings to the proof of the solution of Beltrami equation. The existence of solution of initialregional problems for Beltrami equation with singular point in unlimited area with a section is proved.